Pengungkapan Proses Pengambilan Keputusan Membuat atau Membeli (Make or Buy) Dalam Industri Farmasi Dan Alat Kesehatan (Studi Kasus: PT Rajawali Medika Mandiri) - Niken Fitri Hastuti; Patria Prasetio Adi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
Recent shifts in public procurement policy, notably Indonesia’s mandatory local content requirement (TKDN), aim to substitute imports with domestic production. Many distributors face implementation dilemmas due to constrained upstream supply chains, high initial investment costs, and lengthy certification lead times. This study examines the make or buy decision at PT Rajawali Medika Mandiri, a distributor initiating local production in Indonesia’s medical device and pharmaceutical sectors. Employing a qualitative case-study design, the research draws on six cross-functional in-depth interviews, participant observation, and internal company documents. Trustworthiness was strengthened through methodological triangulation and literature synthesis. Findings show that TKDN and procurement rules increase the relative appeal of local production but their effectiveness is limited by upstream component availability, high start-up expenditures (R&D, certification, testing), protracted certification/ production lead times, and volatile government budgets. The firm uses a stage-gate decision process and explores hybrid transitional strategies (contract manufacturing, strategic alliances). Practical recommendations include multi-criteria decision analysis, financial feasibility assessments for priority products, pilot contract-manufacturing, supplier development, and targeted policy incentives to bolster regulated health-sector domestic capacity.